PROBLEM SOLVING DALAM PSIKOLOGI ISLAM - Pratama, Nurfigita; ahmad, mutia aini (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Humans often face many different problems. Problems can be understood as part of each struggle that is inevitable for every human being. Every problem sometimes feels so heavy, so many people feel very sad when they are in trouble. From an Islamic point of view, humans were created to serve Allah SWT. Belief is even the basis for assessing the quality of a Muslim's personality. Just being a Muslim was never supposed to be a believer before. he can face and complete various tests from Allah SWT wisely. Many people do not have the courage or even the skills to accept deciding to solve a problem, they can even drag on with the problem which can then disrupt their physical, emotional and mental stability. This study uses a type of literature review by obtaining data by collecting data through secondary data sources, whether from books, journals, or related sources. This paper is expected to be able to invite readers to be able to address the problem wisely.keyword: Problem solving, Islamic psychology